Efficiency of Purified Plantaricin from Lactobacillus Plantarum in Preventing P. Aeruginosa from Forming Biofilms Causing Wound Infections - Safa Ahmed Abed (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Abstract: One of the most common harmful bacteria, particularly in hospitals, is Pseudomonasaeruginosa, which is also the most frequent cause of wound infections. Because it leads to antibioticresistance and persistent infections, one of the most significant virulence factors it produces isbiofilm. The goal of the current study is to prevent P. aeruginosa isolates from wound patients fromforming biofilms by using plantaricin, which is a peptide with broad-spectrum antibiotic generated byLactobacillus plantarum. In order to produce plantaricin, so that Lactobacillus plantarum isolates from rawbuffalo milk were screened. The plantaricin was then purified using ammonium salts and a gelfiltration column, with a final 40% recovery. The isolates of P. aeruginosa with more production tobiofilm from wound infections were tested for the inhibitory impact of pure plantaricin. The resultsshowed that the plantaricin reduced the development of biofilms in a dose-dependent manner, with alarger percentage of biofilm inhibition reaching 46–68% at 150 µg/ml.